2009
DOI: 10.1016/j.ygyno.2008.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Identification of human papillomavirus type 16 integration sites in high-grade precancerous cervical lesions

Abstract: 1Objectives. Infection with oncogenic human papillomaviruses (HPV) is a prerequisite 2 for the development of cervical cancer. In many cases of cervical cancer and all cervical 3 cancer derived cell lines oncogenic HPV DNA is found to be integrated, indicating the 4 importance of integration in disease development. In this study, 176 HPV 16 positive 5 precancerous cervical lesions were analyzed for the physical state of viral genome to 6 determine the sites of integration into a host cell DNA and to evaluate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 41 publications
3
50
0
1
Order By: Relevance
“…We also showed that deletions and complex rearrangements frequently occurred in the cellular sequences targeted by the integrations, and the integrations clustered in FRA13C (13q22), FRA3B (3p14.2), and FRA17B (17q23) . Studies from other groups also suggested that chromosome bands that contain CFS regions are the preferred sites for HPV integrations in both cervix carcinoma-derived cell lines and clinical samples [Hidalgo et al, 2003;Dall et al, 2008;Matovina et al, 2009]. Furthermore, we also found a hot spot of HPV18 integrations within one of the CFSs in chromosomal band 8q24 near the c-Myc proto-oncogene [Ferber et al, 2003].…”
Section: Cfss and Large Cfs Genes In Cervical Cancersupporting
confidence: 80%
“…We also showed that deletions and complex rearrangements frequently occurred in the cellular sequences targeted by the integrations, and the integrations clustered in FRA13C (13q22), FRA3B (3p14.2), and FRA17B (17q23) . Studies from other groups also suggested that chromosome bands that contain CFS regions are the preferred sites for HPV integrations in both cervix carcinoma-derived cell lines and clinical samples [Hidalgo et al, 2003;Dall et al, 2008;Matovina et al, 2009]. Furthermore, we also found a hot spot of HPV18 integrations within one of the CFSs in chromosomal band 8q24 near the c-Myc proto-oncogene [Ferber et al, 2003].…”
Section: Cfss and Large Cfs Genes In Cervical Cancersupporting
confidence: 80%
“…Other groups also reported that chromosome bands that contain CFS regions are the preferred sites for HPV integrations in both cervix carcinoma-derived cell lines and clinical samples [Hidalgo et al, 2003;Dall et al, 2008;Matovina et al, 2009]. In addition, we also found a hotspot of HPV18 integration located within one of the CFSs at chromosomal band 8q24 near the c-MYC proto-oncogene [Ferber et al, 2003].…”
Section: Hpv and Cervical Cancersupporting
confidence: 79%
“…Of particular interest was the finding that all of the samples harboring integration in 17q23 were advanced lesions of CINII-III or SCC. The affected gene, TMEM49, also known as the VMP1 (vacuole membrane protein-1), encodes a stress-induced autophagy-associated protein and has been repeatedly reported to be affected by HPV16 integration in high-grade cervical lesions and squamous carcinomas [20,29], making it of particular interest for its role in tumor formation. Another frequently targeted gene is TP63, which acts as a tumor suppressor and has been found to be overexpressed in human cervical cancers cells [30,31].…”
Section: Discussionmentioning
confidence: 99%